Humanising social intervention through comics - Maldonado Lozano, Manuel Jesús; Gutiérrez Zornoza, Myriam; Yubero Jiménez, Santiago (Cuadernos de Trabajo Social, 2022)
We conceptualize reality as a system of multiple domination: capitalist, colonial (power-knowledge-existence) and heteropatriarchal. As a tool for governing behavior, social intervention is increasingly subject to technical-bureaucratic-protocolized expert knowledge, dehumanizing and labeling other non-people. Other narrative-based sources of alternative knowledge such as comics, interpreted as non-technical and subversive, are forgotten. This article is intended to show the potential of the comic as an instrument for social intervention and training of students and professionals in the social sphere. Qualitative research was carried out by selecting 140 comics, creating a movement inspired by Graphic Medicine to explore the capacity of social comics as a useful tool to humanize social intervention.
Keywords: decolonial theories; social intervention; humanization; comic